The Influence of Student Motivation and Learning Strategy on Learning Outcomes in Science - Cagape, Gezer; Israel, Gina Fe (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of student motivation and learning strategies on the science learning outcomes of Grade 10 students in selected public secondary schools in the Pantukan North District, Davao de Oro. Anchored on Zimmerman’s Self-Regulated Learning Theory, Pintrich’s Model of Motivated Learning, and Self-Determination Theory, the study employed a quantitative non-experimental descriptive-correlational design with regression analysis. Data were collected from 259 Grade 10 students selected through stratified random sampling using the adapted Motivation to Achieve Questionnaire (MAQ), the adapted Motivated Strategies for Learning Questionnaire (MSLQ), and students’ official third-quarter science grades. Descriptive statistics, Pearson Product-Moment Correlation, and multiple regression analysis were used to analyze the data. The findings revealed that respondents demonstrated high levels of student motivation and learning strategy use and achieved very satisfactory science learning outcomes. Student motivation and learning strategies were both positively and significantly related to science learning outcomes. Regression analysis further showed that striving for excellence was the strongest predictor among the motivation domains, while resource management was the strongest predictor among the learning strategy domains. These findings indicate that motivated learners who effectively apply learning strategies are more likely to achieve higher academic performance in science. The study recommends strengthening students’ motivation and strategic learning through learner-centered instructional practices, explicit instruction in effective study strategies, and professional development programs that enhance teachers’ capacity to support student motivation and learning. The study supports Sustainable Development Goal (SDG) 4: Quality Education by providing evidence that can improve science instruction and learner achievement, and SDG 9: Industry, Innovation and Infrastructure by promoting scientific literacy, critical thinking, and problem-solving skills essential for innovation. Its findings contribute to educational, institutional, and socio-economic sustainability by informing evidence-based instructional practices that foster improved science learning outcomes.